Exploring adversity and the potential for growth among elite female athletes - Tamminen, K. A.; Holt, N. L.; Neely, K. C. (Psychology of Sport and Exercise, 2013)
Objectives: The purposes of this study were to (a) explore experiences of adversity and (b) to examine perceptions of growth following adversity among elite female athletes. Methods: Semi-structured interviews were conducted with five elite female athletes (ages 18-23 years) who competed internationally in track and field, swimming, long-distance running, and basketball. Interviews were analyzed using an interpretative phenomenological approach (Smith, Flowers, & Larkin, 2009). Results: Incidents of performance slumps, coach conflicts, bullying, eating disorders, sexual abuse, and injuries were reported. The shared `essential` features of participants` experiences of adversity were isolation/withdrawal, emotional disruption, questioning identity as an athlete, and understanding experiences within a context of perceived expectations. It appeared that as participants sought and found meaning in their experiences, they identified opportunities for growth associated with social support and also as they realized the role of sport in their lives. Aspects of growth include realizing strength, gaining perspective of their problems, and gaining a desire to help others. Athletes` experiences with adversity were seen as part of an ongoing journey through elite sport. Conclusions: Athletes` experiences of adversity may have initiated a process of questioning their identities and searching for meaning in their experiences. Findings highlighted the complexity associated with social support and athletes` growth following adversity. Growth following adversity appears to be a valuable area of research among elite athletes.